Impact of routine Newcastle disease vaccination on chicken flock size in smallholder farms in western Kenya - Otiang, Elkanah; Thumbi, Samuel M.; Campbell, Zoë A.; Njagi, Lucy W.; Nyaga, Philip N.; Palmer, Guy H. (Public Library of Science, 2021)
Poultry represent a widely held economic, nutritional, and sociocultural asset in rural communities worldwide. In a recent longitudinal study in western Kenya, the reported mean number of chickens per household was 10, with increases in flock size constrained principally by mortality. Newcastle disease virus is a major cause of chicken mortality globally and hypothesized to be responsible for a large part of mortality in smallholder flocks. Our goal was to determine the impact of routine Newcastle disease virus (NDV) vaccination on flock size and use this data to guide programs to improve small flock productivity.